Radiative recombination in BiI₃(Mn) and BiI₃(Cr) layered single crystals - Motsnyi, F.V.; Dorogan, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The photoluminescence spectra of BiI₃(Mn) and BiI₃(Cr) single crystals were studied. The new bands at λ = 1.1 and λ = 1.83 μm were registered at the temperature 4.2 K. It was shown that the first and second bands arise due to Mn²⁺ and Cr³⁺ ions, accordingly. The experimental results were explained using the configuration model. The energies between minima of configuration curves of excited and basic states for both centres were estimated.